'I Can See it in the Nightclub': Dance, Capoeira and Male Bodies. Issue 1 (February 2014) - Stephens, Neil; Delamont, Sara
This paper reports an ethnographic study of how Brazilians teaching capoeira in the UK use dance as a discursive and embodied pedagogic strategy both to change men's bodies and also to gauge the success of their instructional work. The theoretical framework is drawn from Herzfeld's neglected study of the poetics of manhood in Crete which is revisited in the light of his subsequent analysis of the embodiment of ethnographic practice. Ethnographic research is used to show how British men learning capoeira are enculturated into a different, Brazilian, embodiment in which dance is masculine, and dancing is one way to display a social self-regard. Discourse about performance helps to define the appropriateness of the social self-regard that the capoeira students acquire and display.